Pengembangan Pariwisata Pantai Salopi Terhadap Kondisi Sosial Ekonomi Masyarakat Di Kecamatan Lembang Kabupaten Pinrang.: PANTAI SALOPI KECAMATAN ELEMBANG KABUPATEN PINRANG - Cindy Sasmita Said; Rahmawati Rahman; Idris Taking (Fakultas Teknik Universitas Bosowa, 2022)
The purpose of this study was to determine the factors that influence the socio-economic conditions of the people in the Salopi Beach area, Lembang District, Pinrang Regency, and to find out the strategy for developing a tourism area in the Salopi Beach area, Lembang District, Pinrang Regency. This research requires primary and secondary data. The method used in this research is primary data where this method is obtained by conducting physical surveys or field observations or interviewing respondents and slum indicators at the research location. The analytical method used is Chi-Square analysis and SWOT analysis Based on the results of the analysis of ecotourism development as an alternative to mass tourism development, it is one of the approaches in realizing sustainable and environmentally sound development in coastal areas. with the ability of the individual character of the people of Salopi Beach, Lembang District, Pinrang Regency